Tinjauan Hukum Terhadap Tindak Pidana Perdagangan Orang (Human Trafficking) - Devi Komariah (Sanskara Hukum dan HAM, 2026)
Human trafficking is a complex, multidimensional crime that not only violates human rights but also has far-reaching impacts on victims. This study aims to examine the legal aspects of human trafficking in Indonesia, identify the causal factors and impacts, and analyze mitigation efforts. The method used is normative legal research with a descriptive approach, through a literature review of various relevant primary, secondary, and tertiary legal sources. The results of the study indicate that normatively, Indonesia has a fairly strong legal basis through Law Number 21 of 2007 concerning the Eradication of the Crime of human trafficking, which comprehensively regulates the elements of human trafficking and protection for victims. However, in practice, various obstacles are still found, including weak law enforcement, limited capacity of law enforcement officers, and suboptimal coordination between relevant agencies. Factors that encourage human trafficking include poverty, low levels of education, the influence of patriarchal culture, and technological advances that facilitate perpetrators in carrying out criminal methods. The impacts are not only physical but also encompass psychological, economic, and social conditions, causing victims to experience prolonged trauma and difficulties in reintegrating into society. Efforts to combat human trafficking need to be comprehensive, using an integrated preventive, repressive, and rehabilitative approach. Therefore, strengthening responsive legal policies, increasing the effectiveness of law enforcement, optimizing victim protection, and cooperation at both the national and international levels are needed to bridge the gap between legal norms and their implementation, and realizing sustainable eradication of human trafficking.